Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif dalam Meningkatkan Kemandirian Ekonomi Masyarakat Desa Kaduara Timur Kecamatan Pragaan Kabupaten Sumenep - Halil, Hermanto (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2022)
The efforts to empower the people of East Kaduara Village, Pragaan District, Sumenep Regency have provided knowledge, awareness, and full power of the people in achieving changes to become a more independent society. This study uses qualitative methods, in which the researcher becomes the key instrument. The data collection technique is carried out in a triangulation (combined) manner, the data is inductive in nature, and the results of the research are focused on the core or meaning and not globally. Based on the place of implementation, this research is field research and literature. If reviewed based on its use, this research is applied research (applied research). The research results show that creative economy-based community empowerment activities have gone through 1) The process of creative economy-based community empowerment is carried out through the activities of making creative economic products in Kaduara Timur Village, Pragaan District, Sumenep Regency which includes the stages of implementation. 2) There is potential for natural resources, human resources, and business potential in East Kaduara Village, Pragaan District, Sumenep Regency, it is proven that the community can utilize and develop local potential. 3) By forming community groups, it will be easier to mobilize community empowerment, such as fishermen groups, Gapoktan, and others. 4) Community participation occurs by providing awareness. 5) Training has been given even in 1 year 4-5 times received training. It is hoped that after receiving the training the results can be developed with their group mates.